Was the New Deal Contractionary? - Eggertsson, Gauti B (American Economic Review, 2012)
Can government policies that increase the monopoly power of firms and the militancy of unions increase output? This paper shows that the answer is yes under certain “emergency” conditions. These emergency conditions—zero interest rates and deflation—were satisfied during the Great Depression in the United States. The New Deal, which facilitated monopolies and union militancy, was therefore expansionary in the model presented. This conclusion is contrary to a large previous literature. The main reason for this divergence is that this paper incorporates rigid prices and the zero bound on the short-term interest rate. JEL: E23, E32, E52, E62, J51, N12, N42